Ties That Bind - Woodsmall, Cindy (Colorado Springs, Colorado : WaterBrook Press, 2015)
"An Old Order Amish young woman and an unsuspecting college student are on a collision course that neither could have foreseen"--
Keywords: Amish -- Fiction; Man-woman relationships -- Fiction; College students -- Fiction; Family secrets -- Fiction; Homecoming -- Fiction; FICTION / Romance / Contemporary; FICTION / Christian / Romance; Christian fiction; Romance fiction